Death & the redheaded woman [large type] : an auction block mystery - Ross, Loretta, 1966- (Thorndike Press, 2015)
When auctioneer Wren Morgan begins cataloging the contents of the Campbell mansion, she's unprepared to find something that can't be appraised - a dead man. When the body turns out to be a criminal with ties to a recent jewel heist, Wren meets Death Bogart, a private eye and part-time bounty hunter. Death is searching for the stolen jewels needed to convict a murderer. Death finds a friend and willing ally in Wren, but they aren't the only ones searching for treasure. Two ruthless men are also on the hunt, and they will do anything to eliminate the competition. To survive, Death and Wren must solve two mysteries spanning a century and a half and outwit a pair of cold-blooded killers.